Population, Reproduction and Management of Captive Asian Elephants (Elephas maximus) in Jaldapara Wildlife Sanctuary, West Bengal, India - Baskaran, N.; Das, Subhamoy; Sukumar, R. (Indian Forester, 2009)
The population structure, reproduction and management of captive Asian elephants managed by the Forest Department at Jaldapara Wildlife Sanctuary was studied during 2004. The sanctuary managed 48 captive elephants (18 adults, 17 sub-adults and 13 juvenile) with an overall male to female ratio of 1:2. Although there was no calf in this group during 2004, juveniles constituted a significant (27%) proportion of the population, indicating high reproduction in the preceding years. Selected individuals were used for work 2-3 hours/day, for patrolling and wildlife tourism. The elephants were allowed to graze freely in the natural habitat, as well as provided cut fodder and supplementary diet. There were 16 adult cows of which 13 were breeding regularly, while the remaining three cows were yet to calve though two of them were > 45 yrs. Mean age at first calving in the population was 19.5 yrs. Females born in captivity calved at a younger age (17.2 yrs) as compared to females caught or rescued from the wild (21.7 yrs). Mean inter-calving interval was 4.7 yrs. Sex ratio of 51 calves showed a male-biased sex ratio (1.6 male: 1 female). Middle-aged mothers produced more male calves than female calves as compared to younger or older mothers. A distinct seasonality in calving was observed. Overall, this is a healthy captive elephant population under effective management; we make some suggestions for improvement of this management.